A low‐cost ultrasound model for simulation of paediatric distal forearm fractures. Issue 2 (25th February 2018) - Snelling, Peter James
Abstract: Background: Forearm injuries are a common presentation to the emergency department. Point‐of‐care ultrasound has been demonstrated to be an accurate and well‐tolerated tool in the diagnosis of non‐angulated paediatric distal forearm fractures. Ultrasound model simulation is a practical alternative for ultrasound education. Aims: To describe the construction and validation of a low‐cost ultrasound model for the simulation of non‐angulated paediatric buckle and greenstick distal forearm fractures, for the educational instruction of healthcare providers. Materials & Methods: The materials for the basic paediatric fracture model include turkey or chicken bones soaked in white vinegar to make them pliable, food‐grade gelatine and plastic containers. The fidelity can be improved by using synthetic gelatine set in a cylindrical mould, which can be placed within a manikin forearm. Results: The models were validated by five paediatric emergency nurse practitioners and five paediatric emergency physicians. All participants were able to correctly identify the fracture types. All participants rated the models highly for both realism and educational value, with a preference for the turkey bone model as a better representation of buckle fractures. Discussion: The ultrasound model described in this article can be made from low‐cost materials that can be easily sourced, which facilitates the identification of the different paediatric fracture subtypes, with the additional advantage of not causing discomfort to a child. A limitation of this model includes its inability to simulate the radiolucent epiphysis and represent Salter‐Harris fracture subtypes. Conclusion: This low‐cost, high‐fidelity ultrasound model presents both an accurate and practical educational model for training healthcare providers, with a preference towards the turkey bone model.